Novel characterization of the large water discharge. Issue 4 (4th July 2017) - Sang, Yong; Li, Xiaoxiong
ABSTRACT: Measurement of water discharges is important in chemical engineering and pharmacy. However, high-accuracy measurements of the large water discharge are difficult due to long operational periods and large total water discharge. Here is reported a novel device for the highly accurate, continuous measurement of large water discharge at atmospheric pressure. The device is composed of two identical water discharge measurement subsystems. The computer-controlled system automatically switches the subsystems alternate operation to provide continuous, accurate measurements. Each subsystem used a slender glass tube 2300 mm in length, a pressure transducer, and a solenoid valve. After static calibration, the pressure transducer accurately measures the volume of water in the tube based on the pressure difference in the liquid levels. Moreover, the dynamic error caused by the fluidity of water was characterized. Comparison of simulations and measurements were used to characterize and reduce the dynamic error. Continuous large water discharge measurements were performed. The results show that the device is accurate, stability, and not limited by the measurement time, allowing continuous operation for extended intervals.